Analisis Penerimaan Pengguna Aplikasi Ukrida Virtual Class Menggunakan Technology Acceptance Model 2 - Tirza Unggu; Yudhi Windarto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The Covid-19 pandemic has affected every aspect of life, one of which is the learning system. The learning process that was carried out face-to-face was suddenly forced to adapt to remote learning activities. Because of that, the University implemented a Moodle-based Learning Management System known as Ukrida Virtual Class (UVC). After the implementation in 2 years, it was found that there are still academics who have not used the Ukrida Virtual Class. Technology Acceptance Model 2 (TAM 2) testing was conducted at Krida Wacana Christian University to find out the root causes, behavior and user acceptance of UVC. The variables in this study consisted of 9 variables; Subjective Norms, Image, Job Relevance, Output Quality, Results Capability, Perceived Usefulness, Perceived Ease of Use, Intention to Use, and Usage Behavior. The results show that the Subjective Norm has a significant positive effect on Intention to Use, Perceived Usefulness, and Image. Meanwhile, Image, Job Relevance, Output Quality, Result Demonstrability, Perceived Ease of Use have a significant positive effect on Perceived Usefulness. Perceived Usefulness and Perceived Ease of Use have a significant positive effect on Intention to Use. And Intention to Use has a significant positive effect on Usage Behavior.